Solar photocatalytic gas-phase degradation of n-decane-a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda (2015)
Cellulose acetate monoliths (CAM) were used as the substrate for the deposition of TiO2 films to produce honeycombed photoactive structures to fill a tubular photoreactor equipped with a compound parabolic collector. By using such a setup, an efficient single-pass gas-phase conversion was achieved in the degradation of n-decane, a model volatile organic compound. The CAM three-dimensional, gas-permeable transparent structure with a rugged surface enables a good adhesion of the catalytic coating. It also provides a rigid structure for packing the tubular photoreactor, and maximizing the illuminated catalyst surface. The efficiency of the photocatalytic oxidation (PCO) process on n-decane degradation was evaluated under different operating conditions, such as feeding concentration (73 and 146 ppm), gas stream flow rate (73, 150, and 300 mL min(-1)), relative humidity (3 and 25 %), and UV irradiance (18.9, 29.1, and 38.4 W-UV m(-2)). The results show that n-decane degradation by neat photolysis is negligible, but mineralization efficiencies of 86 and 82 % were achieved with P25-CAM and SG-CAM, respectively, for parent pollutant conversions above 95 %, under steady-state conditions. A mass transfer model, considering the mass balance to the plug-flow packed photoreactor, and PCO reaction given by a Langmuir-Hinshelwood bimolecular non-competitive two types of sites equation, was able to predict well the PCO kinetics under steady-state conditions, considering all the operational parameters tested. Overall, the performance of P25-CAM was superior taking into account mineralization efficiency, cost of preparation, surface roughness, and robustness of the deposited film.